Exploration of the Potential of Reclaimed Waste Cooking Oil for Oil-Immersed Power Transformers - Imran Sutan Chairul; Sharin Ab Ghani; Hidayat Zainuddin; Nor Hidayah Rahim; Mohd Aizam Talib; Nor Hafiz Nor Rahman (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
In this study, reclaimed waste cooking oil is proposed as an alternative insulating liquid for oil-immersed power transformers. Reclamation is carried out by heating a mixture of waste cooking oil and Fuller’s Earth adsorbent and followed by filtration. Propyl gallate antioxidant is then added into the filtered oil. Four oil samples are investigated in this study: (1) new cooking oil (NCO), (2) waste cooking oil (WCO), (3) reclaimed oil (RWCO) and (4) reclaimed oil with propyl gallate antioxidant (RWCOPG). The AC breakdown voltage, moisture content and total acid number is measured for all oil samples according to the ASTM D1816, ASTM D1533 and ASTM D974 standard test method, respectively. The results show that the AC breakdown voltage is highest for the RWCOPG sample (28.08 kV), which is 0.4% higher than the standard requirement of 20 kV. The moisture content for this sample is 180.60 ppm, which is still below the allowable limit of 200 ppm. However, the total acid number is highest for the RWCOPG sample which suggests that it has high acidity. It is indicated that the antioxidant-reclaimed waste cooking oil has potential to be used as an insulating liquid for oil-immersed power transformers, but much work is still needed to reduce the total acid number of this oil.